Hasél II or The criminal prosecution of animosity (about a text by Jacobo Dopico) - Vázquez Alonso, Víctor Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This paper briefly examines the grey areas of the freedom of speech protection system in Spain in connection with the review of the Spanish Supreme Court ruling (number 135/2020) of 7 May 2020 carried out by Jacobo Dopico in the last issue of this journal. This case decides the appeal of the rap artist Pablo Hásel. First, this paper analyzes the factors that led to a restrictive turn in our idea of freedom of speech in order to, subsequently, show the consequences of this trend in the light of Hásel´s case.